(3QSGdI aj fSH Hfi LQehf hGdSbjajjf hGdSQGZfI hJOZjQ hGdMehOjjf hGdLhWjjf hChdGO cKQI hHfi YeQGfs
(3ChdgG (B:s
(3GdMeO ddg ,HfhLQehf GdSbjajhf GdSQGZfI GdMehOjhf GdLhWjhf s
(3BNQgG (B:s
(3gcPG JhLO gPg GdCfSGH ai CjOi GdfGS hdjS Pdc Ydi JMbjb ef NW GdTjN YHO GdbGOQ Ydi GdaGSi HhGSWI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B286 - (3U(B287s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B202 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(487(3O(B) s
Keywords: (3GdJGQjNs